OVERCOMING MENTAL AND EMOTIONAL CHALLENGES IN HIGH SCHOOL STUDENTS: THE ROLE OF THE COUNSELOR IN SCHOOL - Muhyatun, Muhyatun (PT Altin Riset Publishing, 2023)
The researchers wanted to learn more about the part school counselors play in helping high school kids with mental and emotional difficulties. A qualitative approach involving a literature review was employed for this investigation. An in-depth understanding of a topic or phenomena may be gained through a literature review, and the function of school counselors in helping high school students overcome mental and emotional issues is the focus of this particular review. The information was gathered through reading and analyzing a wide range of resources on the subject at hand, including books, scholarly journals, articles, and other papers; from these, the researcher identified overarching themes and drew definitive conclusions. This study's findings highlight the fact that every kid is an individual with their own set of strengths and weaknesses, and that the school counselor's job will change accordingly. High school students' cognitive and affective growth is greatly aided by the services provided by school counselors. Students' mental and emotional health, as well as their overall well-being and potential, can be greatly aided by the counseling and support offered by school counselors.